PENGARUH STRATEGI BELAJAR PQRST TERHADAP SIKAP SOSIAL SISWA PADA MATA PELAJARAN IPS - ., Ni Putu Eka Ariesta Wati; ., Dr. I Made Tegeh, S.Pd., M.Pd.; ., Drs. I Nyoman Murda,M.Pd. (MIMBAR PGSD Undiksha, 2014)
Penelitian ini bertujuan untuk mengetahui perbedaan sikap sosial siswa pada mata plajaran IPS antara kelompok siswa yang dibelajarkan menggunakan strategi pembelajaran PQRST dan kelompok siswa yang dibelajarkan menggunakan strategi pembelajaran konvensional pada siswa kelas V SD di gugus I Kecamatan Buleleng Kabupaten Buleleng.Jenis penelitian ini adalah penelitian quasi eksperimen/eksperimen semu dengan jumlah populasi seluruh siswa kelas V di Gugus I Kecamatan Buleleng Kabupaten Buleleng berjumlah 280 orang dari 11 kelas. Jumlah sampel penelitian 120 orang siswa. Data tentang sikap sosial siswa dikumpulkan dengan metode non tes berbentuk angket/kuessioner. Data yang sudah diperoleh setelah memberikan tes kemudian dianalisis dengan menggunakan analisis statistik deskriptif dan statistik inferensial (uji-t). Berdasarkan analisis data, terdapat perbedaan signifikan antara sikap sosial siswa pada mata pelajaran IPS siswa yang mengikuti pembelajaran menggunakan strategi pembelajaran PQRST (preview, question, read, summarize and test) dan kelompok siswa yang mengikuti pembelajaran menggunakan strategi pembelajaran konvensional pada siswa kelas V SD di gugus I Kecamatan Buleleng Kabupaten Buleleng (thit = 4,49 > ttab = 1,980). Adanya perbedaan yang signifikan menunjukkan bahwa penerapan strategi pembelajaran PQRST(preview, question, read, summarize and test ) dalam pembelajaran IPS berpengaruh signifikan terhadap sikap sosial siswa dibandingkan dengan strategi pembelajaran konvensional. Hal ini berarti strateg pembelajaran PQRST (preview, question, read, summarize and test) berpengaruh positif terhadap sikap sosial siswa mata pelajaran IPS pada siswa kelas V SD di Gugus I Kecamatan Buleleng Kabupaten Buleleng. Kata Kunci : PQRST, Sikap Sosial This study aims to determine the differences in social attitudes of students in social studies IPS among groups of students that learned using PQRST learning strategies and student groups that learned using conventional learning strategies on fifth grade elementary school students at the Cluster 1 of sub-district Buleleng, Buleleng regency. Type of research is a quasi experimental / quasi-experimental, with a population around the fifth grade students at Cluster 1 of sub-district Buleleng, Buleleng regency amounted to 280 people from 11 classes. Total sample of 120 research students. Data collected about students' social attitudes to the non-shaped test questionnaire. Data obtained after giving a test and then analyzed using descriptive statistical analysis and inferential statistics (t-test). Based on data analysis, there were significant differences between the social attitudes of students in social studies students who take learning to use learning strategies PQRST (preview, question, read, summarize and test) and a group of students who take conventional learning using learning strategies on fifth grade elementary school students at the Cluster 1 of sub-district Buleleng, Buleleng regency. (thit = 4,49 > ttab = 1,980). Significant difference indicates that the application of learning strategies PQRST (preview, question, read, summarize and test) in social studies IPS learning significantly influence the social attitudes of students compared with conventional learning strategies. This means learning strategist PQRST (preview, question, read, summarize and test) positive effect on students' social attitudes on social studies IPS in fifth grade elementary school students at the Cluster 1 of sub-district Buleleng, Buleleng regency.keyword : PQRST (preview, question, read, summarize and test), social attitudes.